PERKEMBANGAN MADRASAH HADIS DI BASRAH DAN KUFAH ABAD I-II H: Studi Komparatif Metodologi Periwayatan dan Dampaknya Terhadap Tradisi Keilmuan Islam - Ikfina Ismah Maulana (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
This research examines the dynamics of hadith historiography in Basra and Kufa, two important cities in the development of Islamic sciences. The main issues studied are the characteristics of hadith development in both cities, the key figures involved, and their impact on the development of Islamic scholarship. The research aims to analyze the similarities and differences in hadith narration methodologies, identify the contributions of key figures, and evaluate the influence of these two centers of learning on the hadith tradition as a whole. Using a qualitative method with a historical-comparative approach, this research analyzes relevant primary and secondary sources. The results show that despite similarities in basic narration methodology, the two cities developed different approaches: Basra tended to be conservative and textual with an emphasis on linguistic aspects, while Kufa was more open to the use of ra’yu (reasoning) in hadith interpretation. The interaction between the two cities created a synthesis that enriched the Islamic scholarly tradition. The impact of hadith development in both cities is evident in three aspects: the development of hadith science in general, the formation of fiqih schools, and the spread and preservation of hadith. In conclusion, the dynamics of hadith historiography in Basra and Kufa played a crucial role in shaping the methodological and intellectual foundation for the development of Islamic sciences, with a legacy that remains relevant in contemporary Islamic studies.